PENGARUH SUSTAINABILITY REPORTING TERHADAP NILAI PERUSAHAAN DENGAN INVESTMENT OPPORTUNITY SET SEBAGAI VARIABEL MODERATING - Yovani Gunawan; Sekar Mayangsari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
This study is aimed to determine the effect of Sustainability Reporting on Firm Value with Investment Opportunity Set as moderating variable. The sample used in this research was companies listed in Indonesia Stock Exchange and publish sustainability reports in 2011-2013 which were 18 companies using purposive sampling method. The independent variable was the Sustainability Reporting measured by index value with reference from the sustainability report guidelines of Global Reporting Initiative (GRI). The dependent variable was the Firm Value as measured by the ratio of Tobin's Q. While moderating variables, Investment Opportunity Set was proxied by the market to book value ratio. The results show that the Sustainability Reporting has no significant effect on Firm Value. While the test resulted from Moderated Regression Analysis (MRA) method showed that the Investment Opportunity Set is able to increase the influence positively in relation between Sustainability Reporting and Firm Value.